The Role of Stakeholders in the Strategy of Developing Local Culinary as a Tourist Attraction in the Dieng Highlands of Wonosobo, Central Java - Melati Sukma Klara (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Dieng as a tourist area in Central Java with mountainous tourist attractions, the history and culture they have have great potential in the attraction of culinary tourism. The variety of local culinary owned by Dieng has the potential to become a new culinary tour. Culinary produced by utilizing local agricultural ingredients and processed with traditional recipes for generations. The problem that needs to be analyzed is how the role of stakeholders in the development of culinary tourism and the right strategy to support their potential. This qualitative study collects data through observation, interviews, literature studies, documentation and questionnaires. The theories used for data analysis are stakeholder theory and tourism development theory. The analysis shows that all stakeholders have a positive perspective on the development of Dieng's local culinary. The success of the development of Dieng's local culinary tourism is due to the merger of the roles of all stakeholders. They are already in their respective roles and are already doing well with several culinary programs that are being run. The IE strategy produced in this study shows that the x and y points are in the first quadrant or cell I. This strategy shows that the existing potential is very strong and can be developed with the strategy produced in the SWOT analysis.